2023
DOI: 10.3390/ijerph20021158
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Application of Artificial Intelligence in Public Health Management: Leveraging Artificial Intelligence to Improve COVID-19 CT Image Diagnosis

Abstract: Since the start of 2020, the outbreak of the Coronavirus disease (COVID-19) has been a global public health emergency, and it has caused unprecedented economic and social disaster. In order to improve the diagnosis efficiency of COVID-19 patients, a number of researchers have conducted extensive studies on applying artificial intelligence techniques to the analysis of COVID-19-related medical images. The automatic segmentation of lesions from computed tomography (CT) images using deep learning provides an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Public management involves a large number of processes and tasks, including document processing, data collection, approval processes, etc. Artificial intelligence can improve the efficiency and accuracy of public management through automated processes and robot assistants [3] . Firstly, automated processes refer to the process of using artificial intelligence technology to automate the execution of tedious and repetitive tasks.…”
Section: Automated Processes and Robot Assistantsmentioning
confidence: 99%
“…Public management involves a large number of processes and tasks, including document processing, data collection, approval processes, etc. Artificial intelligence can improve the efficiency and accuracy of public management through automated processes and robot assistants [3] . Firstly, automated processes refer to the process of using artificial intelligence technology to automate the execution of tedious and repetitive tasks.…”
Section: Automated Processes and Robot Assistantsmentioning
confidence: 99%
“…Furthermore, in the future, AI-based applications could be used to help inform the public about health issues [3][4][5]. As an example for how AI be applied, He and co-workers recently showed that a method based on deep learning significantly improved the accuracy of COVID-19 image analysis [9].…”
Section: Introductionmentioning
confidence: 99%